Critical behavior of the disorder-induced Raman modes close to the λ-phase transition in NH4Cl - Yurtseven, H.; Kayişoğlu, D. (Elsevier BV, 2002)
This study gives our analysis of the disorder-induced Raman modes of v7 (93 cm(-1)) and v5 (144 cm(-1)) close to the lambda-phase transition (P = 0) in the NH4Cl crystal. We describe the critical behavior of the frequency shifts for those modes by a power-law formula and using our Raman data we obtain the value of 0.1 for the critical exponent which can also describe the critical behavior of the thermal expansivity and the specific heat of NH4Cl close to its lambda-phase transition (Tlambda = 242.9 K).
Keywords: Thermodynamics; Crystallization; Spectrum Analysis, Raman; Ammonium Chloride